Adsorption Equilibrium Properties of Zn(II) on Activated Carbon Composite of Derived Empty Palm Oil Fruit Bunches with Metal Organic Frameworks Cu(TAC) - Jasmidi, Jasmidi; Zubir, Moondra; Selly, Rini; Pulungan, Ahmad Shafwan; Faradilla, Putri; Rahmah, Siti; Tanjung, Amar Lohot (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
This study aims to determine the adsorption equilibrium of the activated carbon of empty palm oil fruit bunches and KA-Cu(TAC) on Zn(II). Oil palm empty fruit bunches are used as a bio-sorbent in making carbon at a temperature of 5000 C, the resulting carbon is activated using H3PO4 and modified into a composite with metal organic frameworks of Cu metal and terephthalic acid. MOFs and KA-Cu(TAC) composites were produced by reflux method. Activated carbon, MOFS and KA-Cu(TAC) were characterized using XRD. The adsorption process of Zn(II) metal was analyzed using AAS and determined the optimum conditions with various concentrations to determine the adsorption equilibrium. XRD characterization results show that activated carbon has an amorphous structure, while MOFs Cu(TAC) and KA-Cu(TAC) have a crystalline structure. The optimum condition of activated carbon and KA-Cu(TAC) at a concentration of 180 ppm with the appropriate adsorption isotherm model is the Langmuir isotherm.